2007
DOI: 10.1158/0008-5472.can-06-0522
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-Negative Activator Protein 1 (TAM67) Targets Cyclooxygenase-2 and Osteopontin under Conditions in which It Specifically Inhibits Tumorigenesis

Abstract: Activation of activator protein 1 (AP-1) and nuclear factor KB (NFKB)-dependent transcription is required for tumor promotion in cell culture models and transgenic mice. Dominant-negative c-Jun (TAM67) blocks AP-1 activation by dimerizing with Jun or Fos family proteins and blocks NFKB activation by interacting with NFKB p65. Two-stage [7,12-dimethylbenz(a)anthracene (DMBA)/12-O -tetradecanoylphorbol-13-acetate (TPA)] skin carcinogenesis experiments in a model relevant to human cancer risk, transgenic mice exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…In an effort to identify genes that are stimulated by tumor promoter-induced AP-1 activation and inhibited by TAM67, comparative gene expression profiling of mouse epidermis from 12-dimethylbenz(a)anthracene (DMBA)-initiated wild-type or K14-TAM67 transgenic mice with or without exposure to TPA for 6 h was performed. As expected, only a small set of genes was shown to be significantly induced by a tumor promoter and blocked by TAM67 (9). Among them, Srx emerges as a unique target gene whose induction by TPA was blocked by TAM67.…”
Section: Induction Of Srx Expression Bysupporting
confidence: 70%
See 2 more Smart Citations
“…In an effort to identify genes that are stimulated by tumor promoter-induced AP-1 activation and inhibited by TAM67, comparative gene expression profiling of mouse epidermis from 12-dimethylbenz(a)anthracene (DMBA)-initiated wild-type or K14-TAM67 transgenic mice with or without exposure to TPA for 6 h was performed. As expected, only a small set of genes was shown to be significantly induced by a tumor promoter and blocked by TAM67 (9). Among them, Srx emerges as a unique target gene whose induction by TPA was blocked by TAM67.…”
Section: Induction Of Srx Expression Bysupporting
confidence: 70%
“…JB6 cells were cultured in standard conditions with 4% FBS. DNA microarrays, transient transfections, and luciferase reporter assays were performed as previously reported (9). For cell growth and proliferation assay, 10 3 cells were plated in each well of 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, c-Jun family members were shown to play an important role in skin cancer development because K14-driven expression of the TAM67 dominant-negative Jun family construct in the basal layer of the epidermis blocked phorbol 12-tetradecanoate 13-acetate (TPA) or UV-B induced tumors in a skin carcinogenesis model (18)(19)(20). In addition, mice in which c-Jun or JNK2 has been deleted exhibit marked reduction in skin cancer development (21)(22)(23).…”
mentioning
confidence: 99%
“…The molecular events of AP-1 or NF-kB-dependent transcription and eIF4F-dependent translation in carcinogenesis have been a major focus of Dr. Nancy H. Colburn's (Laboratory of Cancer Prevention, Center for Cancer Research, National Cancer Institute, National Institutes of Health) laboratory for a number of years and these were highlighted by Dr. Colburn (77)(78)(79)(80). Activation of AP-1 and NF-kB is necessary to drive tumor promotion and tumor progression and Dr. Colburn's group has demonstrated that the preventive efficacy of the AP-1 blocker TAM67 now extends from skin to mammary and lung carcinogenesis.…”
Section: Promising Agents and Targetsmentioning
confidence: 99%